Synthesis and Characterization of the Manganese Hydroxide Halides Mn(OH)X (X = Br, I) and Crystal Structure of trans-MnBr2·4H2O - Falkowski, Viktoria; Zeugner, Alexander; Isaeva, Anna; Wurst, Klaus; Ruck, Michael; Huppertz, Hubert (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
The pale-pink, hygroscopic compounds Mn(OH)X (X = Br, I) were obtained by high-pressure synthesis in a Walker-type multianvil apparatus. They crystallize in the space group P21/c with a = 640.48(3), b = 698.80(3), c = 615.54(2) pm, β = 110.30(1)° at 183(1) K (X = Br), and a = 686.18(3), b = 713.08(3), c = 637.18(3) pm, β = 109.51(1)° at 150(1) K (X = I). The crystal structures are isotypic to Cu(OH)Cl and consist of edge-sharing distorted Mn(OH)3X3 octahedra arranged in sheets parallel to the bc-plane. Spin-polarized scalar-relativistic DFT+U calculations predict an intrinsic magnetic insulating state (ca. 3.5 eV bandgap) that is proximate to frustration. Calculated effective magnetic moments equal to 4.34 μB/f.u. for Mn(OH)Br and 4.33 μB/f.u. for Mn(OH)I. FT-IR spectroscopy confirmed interlayer hydrogen bonding. As a side result of the experiments, the compound trans-MnBr2·4H2O was obtained. It crystallizes in the space group Cmcm with a = 438.64(2), b = 1167.84(6), and c = 730.95(4) pm.
CRIS-Team Scopus Importer:2022-04-14
Keywords: High-pressure synthesis; Hydroxide halide; Layered compounds; Manganese; Single-crystal